Amentoflavone from Selaginella tamariscina as a potent inhibitor of gut bacterial β-glucuronidase: Inhibition kinetics and molecular dynamics stimulation. (1st May 2021) - Tian, Xiang-Ge; Yan, Jian-Kun; Sun, Cheng-Peng; Li, Jing-Xin; Ning, Jing; Wang, Chao; Huo, Xiao-Kui; Zhao, Wen-Yu; Yu, Zhen-Long; Feng, Lei; Lv, Xia; Ma, Xiao-Chi
Abstract: Gut bacterial β -glucuronidase (GUS) plays a pivotal role in the metabolism and reactivation of a vast of glucuronide conjugates of both endogenous and xenobiotic compounds in the gastrointestinal tract of human, which has been implicated in certain drug-induced gastrointestinal tract (GI) toxicity in clinic. Inhibitors of gut microbial GUS exhibited great potentials in relieving the drug-induced GI toxicity. In this study, Selaginella tamariscina and its major biflavonoid amentoflavone (AMF) were evaluated for their inhibitory activity against Escherichia coli GUS. Two selective probe substrates for GUS (a specific fluorescent probe substrate for GUS, DDAOG and a classical drug substrate for GUS, SN38G) were used in parallel for charactering the inhibition behaviors. Both the extract of S. tamariscina and its major biflavonoid AMF displayed evident inhibitory effects on GUS, and the IC50 values of AMF against GUS mediated DDAOG and SN-38G hydrolysis were 0.62 and 0.49 μM, respectively. Inhibition kinetics studies indicated that AMF showed mixed type inhibition for GUS-mediated DDAOG hydrolysis, while displayed competitive type inhibition against GUS-mediated SN-38G hydrolysis, with the K i values of 0.24 and 1.25 μM, respectively. Molecular docking studies and molecular dynamics stimulation results clarified the role of amino acid residues Leu361, Ile363, and Glu413 in the inhibition of AMF on GUS. These results provided some foundations for the potential clinical utility of S. tamariscina and its major biflavonoid AMF for treating drug-induced enteropathy. Graphical abstract: Image 1 Highlights: Selaginell a tamariscina extract displayed strong inhibitory effects on GUS. .►Amentoflavone was identified as the key inhibitory component in S. tamariscina . .►The inhibition constant and the inhibition mechanism were well-characterized.